Janus onions of block copolymers via confined self-assembly. (12th June 2019) - Cui, Tingting; Li, Xingye; Dong, Bin; Li, Xiang; Guo, Mengxue; Wu, Lixin; Li, Baohui; Li, Haolong
Abstract: Droplet-confined assembly is a powerful tool to fabricate functional nanostructures of block copolymers (BCPs), where the interfacial interaction plays a crucial role. Here, we report an unconventional strategy of using interfacial phase separation to control this assembly. The key lies in the use of an elaborately designed binary surfactant system to tune the interfacial configuration of droplets and realize an asymmetrically directed assembly of BCPs inside droplets, which finally creates unprecedented Janus onion particles with solid surfactant-like properties, e.g., as stabilizers for Pickering emulsions. The formation of Janus onions is due to the strong longitudinal selective interaction and the strong lateral phase separation at the droplet interfaces, provided by our surfactant system. This concept of interfacial phase separation directed assembly not only enriches the routes to controllable assembly of BCPs, but also offers an innovative paradigm to construct distinct regions on droplet surfaces, illuminating potential functions such as smart encapsulation and delivery. Graphical abstract: Image 1 Highlights: 1. Interfacial phase separation of emulsion droplets was firstly used to direct the droplet-confined assembly of block copolymers. 2. Unprecedented Janus onion-like particles of block copolymers were fabricated. 3. The Janus onions could act as particulate surfactants to stabilize Pickering emulsion.